Disciplined Interdisciplinarity - Jasper, David (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
Interdisciplinarity is a word often used in contemporary universities, but little understood or practiced. “Professionalism” tends to keep academics within the narrow boundaries of their own field of research. Dorota Filipczak has long represented a different and more vibrant form in interdisciplinarity which this essay seeks to explore through a brief review of the two journals Literature and Theology and Text Matters, as well as Dorota’s early research and writing on Canadian literature and Malcom Lowry in particular. These suggestions are within the tradition of J. H. Newman’s great vision of a university in the middle of the nineteenth century, and the discussion concludes with a reflection on the conference organized by Dorota in 1998 entitled Dissolving the Boundaries.